Relationship between peritoneal permeability with inflammation and subclinical atherosclerosis in peritoneal dialysis patients (Annals of Medical Research, 2021)
None
Keywords: s: Atherosclerosis; Inflammation; Peritoneal Dialysis; Peritoneal Permeability.